Effects of thermal processing and thermosonication on quality of honey from stingless bees - Chong, Kar Yeen (2017)
One of the distinctive characteristics of stingless bee honey is its higher moisture content than honeybee honey. Honey being a supersaturated sugar solution tends to crystallize and ferment easily. The objective of this research was to study the effects of thermal processing and thermosonication on the quality of a stingless bee honey in Malaysia, the Kelulut. A two-factor-five-level design was adopted and the factors were processing temperature ranging from 45 to 90 °C and processing time ranging from 30 to 120 minutes for both methods. Physicochemical properties including water activity, moisture content, colour intensity, viscosity, hydroxymethylfurfural (HMF) content, total phenolic content (TPC), and radical scavenging activity (RSA) were determined. Thermosonicated honey had its water activity and moisture content reduced by 7.9% and 16.6%, respectively compared to 3.5% and 6.9% by thermal processing. Thermosonicated honey had its colour intensity increased by 68.2 %, viscosity increased by 275.0%, TPC increased by 58.1%, and RSA increased by 63.0% when compared to its raw form. The increase in HMF to 62.46 mg/kg using thermosonication was within the limits of international standards. The second objective of this study was to optimise thermal processing and thermosonication conditions using response surface methodology (RSM) based on minimum water activity, moisture content, and HMF content while maximizing colour intensity, viscosity, TPC, and RSA. The optimum conditions for thermal processing were at 90 °C for 108 minutes while for thermosonication it was at 90 °C for 111 minutes. To examine potential anti-inflammatory effects of the honey samples, the ability of the optimized Kelulut honey to inhibit nitric oxide production in lipopolysaccharide (LPS)-stimulated murine macrophages, RAW 264.7 cells, was evaluated. Results showed that Kelulut honey was able to both inhibit and stimulate nitric oxide using honey concentrations of 10, 20, and 50 μg/mL. Additionally, Kelulut honey promotes cell growth of RAW 264.7 cells. Thermosonication was revealed to be an effective honey processing alternative to current practices and the use of Kelulut honey as a functional food is proposed.